HERMENEUTIKA HADIS MAHMUD ABŪ RAYYAH DALAM KITAB ADHWA` ALA AL-SUNNAH AL-NABAWIYYAH (KAJIAN ‘ADALAH AL-SAHĀBAH) - Sobirin, Muhammad (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2014)
This article tries to criticize the term ‘adalah al-shahabah by elaborating the work of Abu Rayyah titled  Adhwa` Ala Al-Sunnah Al-Nabawiyyah. For him, ‘adalah shahabah is not a final concept and taken for granted. Then he deconstructs this concept and makes a new conception. In sum, Abu Rayyah ideas that place shahabah under criticism is one of the idea  to refresh Islamic thought where in Shahabah era, it was common to criticize a shahabah to another.